O púlpito como cátedra: retórica e educação nos sermões do Pe. Antônio Vieira (1608-1697) - Nascimento, Rodson Ricardo Souza do (2007)
This work aims to analyze the relationship among culture, education and rhetoric on the sermons of the Priest Antonio Vieira (1608-1697). It discusses the presence of oratory on the Western teaching since its Greek origins until the formation of the Ratio Studiorum in 17th-century. Brazilian society is defined as baroque and the rhetoric arises as element essential in the elaboration of the social imaginary speeches and, occupying as an essencial element in the elaboration of discursese and social imaginaries, occupying the centre of controversies, about questions like reason and the faith, ethics and the politics, the nature of the Indian and African peoples, even over the own construction of the modern subject. In this context the vieira´s preaching discharges the functions of kerigma (preaching), didachê (education) and politics (action). The research consisted in a finicky reading over five of these sermons that were returned in the presence of different audiences. The pulpit was the cathedra where Vieira used his sermons as a manner of social mobilization that aimed not only teaching a determined knowledge of reality, but altering cruel situations like Indian and poor people slavery in his epoch. Education by Vieira consist in a tension between utopian hopes and urgencies of practice. The rhetorical tradition affirms the interdependence of technical ethics and politics aspects. To know is not enough is necessary to convince and to move, realizating passage from theorical to practical liverly. It presupposes still the preoccupation with the solidity of argumentation and of reasoning, a wide cultural formation, the requirement of a civic ethics and, mainly, the adequacy between content and the specifics of audience